Effects of monensin sodium and Xylanase on broiler growth performance - Howell, Amanda; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Antimicrobials, such as monensin sodium, have been used for years in poultry diets to increase digestibly. Recently there has been a push to limit antimicrobial use in poultry feed. To appease this demand, a potential alternative to antimicrobial feed supplement is an enzyme. Exogenous xylanase has been known to improve digestibility in higher fiber diets. Consequently, the objective was to find wither or not xylanase could replace monensin sodium to improve feed digestibility in differing fiber levels of a poultry diet. Six treatments consisting of corn or wheat-based diet supplemented with either 0.10g/kg monensin sodium (Coban90; Elanco Animal Health, Greenfield, IN) or 16,000 BXU/kg beta1-4, endo-xylanase enzyme (Econanse XT;AB Vista, Marlborough, UK) were fed to 206 Cobb chicks (6 birds/cage and 6 cages/treatment). Birds were fed ad libitum in battery cages for 21 days, while body weight and feed intake were recorded weekly. Results indicate that xylanase does improve nutrient digestibility in wheat-based diets to that of a corn-based one. However, there was a limited impact reported for feeding an antimicrobial in this environment.
Keywords: Spring 2017